Improving Students’ Vocabulary Skills Using Word Wall Media in Grade Seventh Students at SMP Negeri 2 Wamena - Friska Simatupang; Dwi Puspitosari; Lestari Batubara (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to improve the English vocabulary mastery of seventh-grade students at SMP Negeri 2 Wamena through the use of Word Wall media. The background of this study is the low vocabulary mastery of students caused by monotonous conventional teaching methods and the lack of attractive visual media. This study used a Classroom Action Research (CAR) design consisting of two cycles, with 20 students selected through purposive sampling as research subjects. Data were collected through tests (pre-test and post-test), observation sheets, and questionnaires. The results showed a significant increase in students' vocabulary skills, where the average score increased from 51.9 in the pre-test to 65.7 in cycle I, and reached 78.05 in cycle II. At the end of cycle II, 90% of students successfully achieved the Minimum Completion Criteria (KKM) of 70. In addition to academic improvement, the use of Word Wall combined with interactive activities and competitive games also succeeded in increasing students' active participation from 60% to 90%, as well as building their confidence and motivation in learning English. Thus, it can be concluded that the Word Wall media is an effective, practical, and enjoyable tool for improving students' vocabulary mastery.